Autoantibodies associated with primary biliary cholangitis are common among patients with systemic lupus erythematosus even in the absence of elevated liver enzymes. (29th September 2020) - Ahmad, A.; Heijke, R.; Eriksson, P.; Wirestam, L.; Kechagias, S.; Dahle, C.; Sjöwall, C.
Summary: Knowledge of concomitant autoimmune liver diseases (AILD) is more detailed in primary Sjögren's syndrome (pSS) compared to systemic lupus erythematosus (SLE). Herein, the prevalence of autoantibodies associated with autoimmune hepatitis (AIH) and primary biliary cholangitis (PBC) was investigated in stored sera from patients with SLE ( n = 280) and pSS ( n = 114). Antibodies against mitochondria (AMA), liver–kidney microsomal (LKM) antigen, smooth muscle (SMA) and anti‐nuclear antibodies (ANA) were analysed with immunofluorescence microscopy. In addition, AILD‐associated autoantibodies were tested with immunoblot. Prior to sampling, eight SLE (2·9%) and three pSS (2·6%) cases were diagnosed with AILD. Among SLE‐cases without known AILD ( n = 272), 26 (9·6%) had PBC‐associated autoantibodies, 15 (5·5%) AIH‐associated autoantibodies (excluding ANA) and one serological overlap. Most subjects with PBC‐associated autoantibodies had liver enzymes within reference limits (22 of 27, 81%) or mild laboratory cholestasis (two of 27, 7·4%), while one fulfilled the diagnostic PBC‐criteria. AMA‐M2 detected by immunoblot was the most common PBC‐associated autoantibody in SLE (20 of 272, 7·4%). The prevalence of SMA (4·4%) was comparable with a healthy reference population, but associated with elevated liver enzymes in four of 12 (25%), none meeting AIH‐criteria. The patient with combined AIH/PBC‐serology had liver enzymes within reference limits. Among pSS cases without known AILD ( n = 111), nine (8·1%) had PBC‐associated, 12 (10·8%) AIH‐associated autoantibodies and two overlapped. PBC‐associated autoantibodies were found as frequently in SLE as in pSS but were, with few exceptions, not associated with laboratory signs of liver disease. Overall, AILD‐associated autoantibodies were predominantly detected by immunoblot and no significant difference in liver enzymes was found between AILD autoantibody‐negative and ‐positive patients. Abstract : In this study, IgG‐autoantibodies associated with autoimmune hepatitis and primary biliary cholangitis (PBC) were found in a considerable proportion of well‐characterized patients diagnosed with primary Sjögren's syndrome and systemic lupus erythematosus (SLE) but without known liver involvement or autoimmune liver disease (AILD). PBC‐associated autoantibodies have previously not been reported in a substantial percentage of cases with SLE. However, the association between autoantibody findings and AILD was poor as no significant difference in liver enzymes was observed between AILD‐associated autoantibody negative and positive patients.